(untitled) (Cambridge, U.K.,New York, 2003)
Providing fresh insights into the interaction between politics and business in twentieth-century Europe, this book indicates the complexity of the relationship--particularly in the environment of the 1920s and 1930s--when fascism was at its height. Distinctive contributions are also made regarding the contrasting behaviors of businessmen and institutions in response to the Great Depression; the rise of Hitler and the "Jewish question"; the role of business networks in the politics of Belgium and Greece; and the business-politics dimension in the formation of the Irish Republic.
Keywords: Chính sách công nghiệp,Business and politics,Industrial policy,kinh doanh và chính trị; Thế kỷ 20,20th century,20th century.,Thế kỷ 20; Châu Âu,Europe,Europe,Châu Âu